Two-Phase Flow and Heat Transfer during Steam Condensation in a Converging Microchannel with Different Convergence Angles. (19th November 2013) - Fu, Ben-Ran; Chang, T. H.; Pan, Chin
Abstract : The present study experimentally investigates the effect of convergence angle of microchannel on two-phase flow and heat transfer during steam condensation. Three condensation regimes, from the inlet to the outlet, are identified: mist/annular flow, injection flow, and slug-bubbly flow. Flow pattern maps are constructed using superficial vapor and liquid velocities as the coordinates, wherein relatively distinct boundaries between the flow patterns can be identified. The experimental results show that the condensation heat flux increases with an increase in the convergence angle and/or the steam mass flux at a given coolant flow rate but decreases with an increase in the coolant flow rate at a given steam mass flux. The results further demonstrate that the local condensation heat transfer coefficient in the mist/annular flow region is much higher than that in other condensation regimes. Moreover, the local condensation heat transfer coefficient in the mist/annular flow and injection flow region decreases with an increase in the convergence angle.